Status of Freshwater Aquaculture in Gujarat: A Trend Analysis and Potential - Chaudhari, A. K.; Ail, Sunil Kumar S.; Misra, C. K.; De, H. K.; Rathod, Ramesh; Bhatt, J. H.; Swain, S. K. (International Journal of Bio-resource and Stress Management, 2023)
This study was undertaken during 2022 in the Regional Research Center of ICAR-Central Institute of Freshwater Aquaculture, Anand, Gujarat, India to study the present status and potential in the development of freshwater aquaculture in the state of Gujarat. The present seed production (2608.37 million fry) and Inland fish production (0.158 MT) in Gujarat is forecasted to reach 3100 million fry and 0.22 MT in 2030; 4600 million fry and 3.14 MT in 2050, respectively. The Regional Research station of ICAR-CIFA had contributed significantly in promoting aquaculture by imparting skill training and providing technical backup to fish farmers. Authors argue that in order to further develop freshwater aquaculture value chain, concerted efforts are required to disseminate technology packages for fish breeding and seed rearing, semi-intensive culture practices, diversified fish farming, scientific management (fish feed and nutrition, water quality and fish health), ornamental fish farming, pearl production and cluster-based fish farming. However, successful implementation of suggested points will be depending on the sustainable adaptive capacity of the freshwater aquaculture producers, entrepreneurs, strategies and planning of policy makers and line departments of various state departments, input dealers and buyers in the state of Gujarat. Hence, they need to be supported in terms of skill, policy and market towards establishing a vibrant fish value chain. Therefore, adoption of BMPs, nurturing entrepreneurs, aggregating farmers and strengthening extension services are recommended.